Measurement of the production cross sections for a Z boson and one or more b jets in pp collisions at √s=7 TeV - Chatrchyan, S.; Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; et al. (SPRINGER, 2014)
The production of a Z boson, decaying into two leptons and produced in association with one or more b jets, is studied using proton-proton collisions delivered by the LHC at a centre-of-mass energy of 7 TeV. The data were recorded in 2011 with the CMS detector and correspond to an integrated luminosity of 5 fb(-1). The Z(ll) + b-jets cross sections (where ll = mu mu or ee) are measured separately for a Z boson produced with exactly one b jet and with at least two b jets. In addition, a cross section ratio is extracted for a Z boson produced with at least one b jet, relative to a Z boson produced with at least one jet. The measured cross sections are compared to various theoretical predictions, and the data favour the predictions in the five-flavour scheme, where b quarks are assumed massless. The kinematic properties of the reconstructed particles are compared with the predictions from the MadGraph event generator using the pythia parton shower simulation.
Keywords: Jet physics; Hadron-Hadron Scattering; Physics